Peran Komunikasi Positif Guru Kelas Dalam Penanggulangan Perundungan Di SDN 1 Bandung Jombang - Muzhaqi, Fahisya Mauline; Raharja, Hawwin Fitra (IJPSE Indonesian Journal of Primary Science Education, 2026)
Bullying in elementary schools remains a significant issue that can negatively affect students’ psychological and academic development. Teachers play an important role in preventing and addressing bullying through effective communication with students. This study aims to analyze the role of classroom teachers in implementing positive communication as a strategy to address bullying in elementary schools. This research employed a descriptive qualitative approach conducted at SDN 1 Bandung Jombang. The research participants consisted of one principal, three classroom teachers of grades IV– VI, and one student selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that teachers apply positive communication through polite language, empathetic interaction, appreciation and praise, open discussion, and educational consequences. These strategies contribute to creating a supportive classroom climate and reducing verbal and social bullying behavior. Supporting factors include collaborative school culture and teacher role modeling, while inhibiting factors involve diverse student characteristics and limited awareness about bullying. This study concludes that positive communication plays both preventive and curative roles in addressing bullying in elementary schools.